Spiritual Leadership Model as a Paradigm for Nursing Leadership: A Review Article - jahandar, parivash; Zagheri tafreshi, Mansoureh; Rassouli, Maryam; Atashzadeh-Shoorideh, Foroozan (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: The aim of this study was to explain how the spiritual leadership model could be used as a paradigm for nursing leadership. Nursing leaders play a critical role in the management of the health care system. Spiritual leadership is a new area that has recently been considered in nursing management. Methods: In this review article, electronic databases (PubMed, Scopus, Google Scholar and Science Direct) were searched from September 2014 to July 2016 to find relevant articles using keywords, such as spirituality, leadership, management, nurses and motivation. In this regard, the articles that fulfilled the goals of the study that were written in English or Persian, had their full texts accessible, and were published in the intended time interval were entered in the study. The articles without authors’ names and dates and non-scientific papers were excluded from the study. On the whole, a total of 120 articles were obtained, of which 48 were selected and analyzed. Results: A review of the literature focusing on spiritual leadership demonstrated that the spiritual leadership model has been examined in different countries, various fields of the industry, trade training, and the health system with positive individual and organizational consequences. It seems that the characteristics of this style of leadership fits the nursing profession as well. Of course, more large-scale future studies for testing this model of leadership in the field of nursing will bring about more promising results. Conclusions: Spiritual leadership could improve the organizational productivity and employees’ satisfaction. Nursing leaders should have paid greater attention to this type of leadership to achieve positive organizational outcomes; therefore, they need more training in this issue..